Side effects-avoided theranostics achieved by biodegradable magnetic silica-sealed mesoporous polymer-drug with ultralow leakage. (December 2018) - Li, Chengyi; Wang, Yi; Du, Yilin; Qian, Min; Jiang, Huilin; Wang, Jianxin; Murthy, Niren; Huang, Rongqin
Abstract: The development of drug delivery vehicles without side effects to normal physiological tissues represents an urgent challenge for safety and effective nanomedicine. Herein, a multifunctional drug delivery vehicle with ultralow leakage was presented, containing an ordered mesoporous resin as a polymer core and homogeneous Fe nanodots-doped silica as the biodegradable shell. In this core-shell structure, the Fe-doped silica shell acts as a compact inorganic cap to seal doxorubicin into the mesoporous polymer cores, but also serves as a superparamagnetic agent for magnetic targeting and magnetic resonance imaging (MRI). Importantly, the caps can be opened via Fe extraction-induced degradation to slowly release the loaded drug under the acidic tumor environment, while achieving ultralow drug leakage under normal in vivo blood circulation (physiological environment). This unique core-shell nanospheres with ultralow drug leakage were demonstrated to achieve side effects-avoided targeting chemotherapy guided by MRI with improved therapeutic outcomes, which showing great potential for efficient cancer theranostics. Graphical abstract: Side effects-avoided targeting chemotherapy guided by MRI was achieved based on the multifunctional core-shell nanomedicine with ultralow leakage, where the Fe-doped silica shell acted as the compacted inorganic caps to well seal the anticancer drug doxorubicin into the ordered mesochannels of polymer cores under normal physiological conditions but biodegrade under acidic tumor environments.Image 1